A Preliminary Mineralogical Examination of the Yamato-74 Achondrites - Takeda, Hiroshi; Miyamoto, Masamichi; Yanai, Keizo; Haramura, Hiroshi (1978)
P(論文) Seven diogenites, two eucritic polymict breccias and one pallasite have been identified in the Yamato-74 meteorites by the electron microprobe and single crystal X-ray diffraction techniques. The texture of Yamato-74010,-74011,-74013,-74037,-74097,-74136 and -74648 is unlike those of the other diogenites. It is not brecciated and texturally the pyroxene seems to have recrystallized to a granoblastic texture with small change in mineral composition. The chemical composition of the orthopyroxenes in these diogenites falls in the range (Ca)_<1.9> (Mg)_<75.1> (Fe)_<23.0> to (Ca)_<3.0> (Mg)_<71.0> (Fe)_<26.0>. The chemistry and textures of these diogenites are the same as those of the Yamato-6902 (b) diogenite previously reported. These Yamato diogenites may represent fragments of the same fall. Yamato-74159 is a polymict breccia which contains mineral and lithic clasts common to eucrites. The Yamato-74450 eucrite shows a variolitic texture, indicating a rapid solidification near the surface of its parent body. A brecciated part containing a pigeonite crystal with augite lamellae is also found in small amounts. The pyroxene trends of Yamato-74450 resemble those of the Pasamonte eucrite. The Yamato-74044 pallasite is the only stony-iron meteorite among the Yamato collection. A preliminary examination of the Yamato-75 meteorites identified one iron-rich diogenite and two eucritic polymict breccias. Yamato-75032 is the most Fe-rich of any known diogenite. departmental bulletin paper